Therapeutic Cancer Vaccine and Combinations With Antiangiogenic Therapies and Immune Checkpoint Blockade - Mougel, Alice; Terme, Magali; Tanchot, Corinne (Frontiers in Immunology, 2019)
Considering the high importance of immune surveillance and immune escape in the evolution of cancer, developing immunotherapeutic strategies have become a major research field in the past decades. The considerable therapeutic breakthrough observed when targeting immune checkpoint receptors have highlighted the need of finding approaches enabling the induction and the proper activation of an immune response against cancer. In this context, therapeutic vaccination, which can induce a specific immune response against tumor antigens, is an important approach to consider. However, this strategy has shown its advantages and limits. Considering its low efficacy in clinic, the approaches combining therapeutic cancer vaccine strategies with other immunotherapies or targeted therapies have been emphasized. This review will discuss the various designs of cancer vaccines with an importance given to the vaccine’s target(s) and delivering strategies. Highlighting advantages and limits of vaccine strategies alone, we will then provide a description of combinatorial strategies associating therapeutic vaccine together with antiangiogenic therapies or immune checkpoint blockade. Antiangiogenic therapies and immune checkpoint blockade have proven their efficacy in clinic for some indications but they still present toxicity and resistance development. Their combination with therapeutic vaccines could be a way to improve therapeutic outcome by specifically stimulating the immune system and considering a global approach of the tumor microenvironment remodeling.